Hemoglobin response to iron-folic acid supplementation and associated factors among anemic pregnant women attending the University of Gondar Comprehensive Specialized Hospital ANC ward Northwest, Ethiopia 2023: A longitudinal follow up study - Asefu Fekadie; Bisrat Birke Teketelew; Melak Aynalem; Aregawi Yalew (PLoS ONE, 2025)
Background Anemia is the most frequent complication during pregnancy. Iron and folate deficiencies are the primary causes of anemia during pregnancy resulting from low hemoglobin concentration. Globally, preventive strategies such as iron and folic acid supplementation, improved dietary practice and deworming program play a crucial role in reducing the rate of anemia. Hemoglobin is improved as a result of iron-folic acid supplementation, though some factors affect good response. Due to limited studies to the study area, the main aim of this study was to assess the hemoglobin response to iron-folic acid supplementation and associated factors among anemic pregnant women. As iron and folic acid supplementation is the key intervention to reduce maternal and fetal complication, this study provides critical insights into the effectiveness of the intervention on improving hemoglobin level and can inform global maternal health strategies, particularly in resource limed settings where anemia remains a major public health concern. Methods A longitudinal follow up study was conducted on a total of 357 anemic pregnant women at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia from June to October 2023. Simple random sampling technique was employed to select the study participants. Data were collected using pretested structured questionnaires. Hemoglobin was determined using Sysmex kx21n hematological analyze. Direct wet mount examination was performed to determine intestinal parasites. Moreover, serological tests were screened using rapid test kit immunochromatographic technique. Data was entered in to Epi-data version 4.6 software and exported to SPSS version 20 for analyses. Paired sample t-test was utilized to determine the change in hemoglobin. Both bi-variable and multivariable logistic regression were done to determine factors associated with the poor response of iron folic acid supplementation. A p-value of < 0.05 was considered as statistically significant. Results The overall good hemoglobin response after IFA supplementation was 188/357 (52.7%). The median (IQR) of Hb was increased from 10.3 (9.6–10.49) gm/dL at baseline to 10.73 (9.78–12.0) gm/dL. Factors associated with poor hemoglobin response were residence (AOR = 2.4, 95% CI: 1.1 5.2), duration of IFA supplementation (AOR = 2.2,95% CI: 1.2, 3.7), intestinal parasite (AOR = 2.8, 95% CI: 1.3, 6.3), meat feeding habit less than two times per week (AOR = 1.7, 95% CI: 1.04, 2.9), green leaf vegetable and fruit feeding habit less than two times per week (AOR = 2.5,95% CI: 1.4, 4.0), coffee drinking habit (AOR = 1.9, 95% CI: 1.14, 3.3), parity (multiparous) (AOR = 2.9, 95% CI: 1.09, 7.2), HBsAg & HCV (AOR = 2.5, 95 CI: 1.15, 5.8) and stage of pregnancy (AOR = 4.0 95% CI (1.9,8.7). These factors in this study, showed significant association with poor hemoglobin responses. Conclusion Hemoglobin level changed significantly from base line to end line. In this study, less than half of the study participants had poor hemoglobin response due to the aforementioned factors. Therefore, focused policies, health care facilitators and providers should strengthen efforts to provide information and create awareness about the benefits of iron and folic acid supplementation during pregnancy.